Apakah circuit training dengan bola dapat meningkatkan kondisi fisik pemain sepakbola junior? - Khalifatullah, Adli; Permadi, Asep Angga; Hermawan, Irwan (Sepakbola, 2024)
Tujuan penelitian ini adala untuk menguji pengaruh program latihan circuit ini menggabungkan latihan bola dengan latihan fisik yang melibatkan berbagai aspek fisik. Masalah pada penelitian ini adalah terdapat pengaruh latihan Circuit Training dengan bola dalam meningkatkan kondisi fisik pemain SSB Jagur. Metode yang diterapkan adalah pretest mendapatkan nilai skor minimum 16.00 dan nilai skor maximum 26.00 nilai rata-rata/mean 19.909. Kesimpulan dari hasil pre-test 19.909 dan hasil post-test 31.681, 11.77% terdapat pengaruh signifikan pengaruh latihan Circuit Training dengan bola dalam meningkatkan kondisi fisik pemain sepakbola SSB Jagur dan meningkatkan sebesar 37% setelah memberikan treatmean sebanyak 16 pertemuan   Can Circuit Training with a ball improve the physical condition of junior football players?   Abstract: This study aimed to examine the effect of circuit training with a ball on the physical fitness of youth soccer players. A one-group pretest-posttest design was employed involving 22 students from SSB Jagur. The subjects participated in a circuit training program with a ball for a total of 16 sessions. Physical fitness was measured before and after the intervention using a series of physical tests (30 m sprint, Illinois Agility Run Test, Standing Broad Jump, push-up, sit-up, back-up, Sit and Reach, and Bleep Test). Data were analyzed using a paired sample t-test with the assistance of SPSS version 20. The results showed a significant improvement in the players’ physical fitness after completing the circuit training program. The average physical fitness score increased from 19.91 (pretest) to 31.68 (posttest). Nearly all components of physical fitness, including strength, speed, agility, endurance, and flexibility, improved. The paired sample t-test indicated a statistically significant difference (p < 0.05), suggesting that circuit training with a ball was effective in enhancing the physical fitness of junior soccer players.